Task Commitment pada Mahasiswa Suku Bugis yang Merantau - Andi Ahmad Ridha (Faculty of Psychology, Universitas Gadjah Mada, 2018)
Settled foreigner college students’ task commitment becomes an important issue due to the demands to commit to themselves and to complete academic tasks. This study uses a quantitative approach and aims to perceive the effect of autonomy towards task commitment on college students of the Bugis tribe settled foreigner. The participants in this study are 96 college students of the Bugis tribe. Data were collected using the autonomy scale and task commitment scale. Results show that autonomy is a contributive factor towards task commitment with an amount up to 39,1% and the remnant is followed by other factors. The Bugis tribe settled foreigner college students has a high task commitment with an amount of up to 62.5% and moderate task commitment with an amount of up to 37.5%. Autonomy in college students has an effect on the degree of task commitment on the Bugis tribe college students. Abstrak.Task commitment pada mahasiswa yang merantau menjadi penting karena mahasiswa dituntut untuk dapat berkomitmen pada diri sendiri dalam tugas-tugas dan menyelesaikan tuntutan akademik di perguruan tinggi. Penelitian ini merupakan penelitian kuantitatif yang bertujuan untuk mengetahui pengaruh kemandirian terhadap task commitment pada mahasiswa suku Bugis yang merantau. Pengambilan data dilakukan dengan menyebarkan skala kemandirian dan task commitment pada 96 orang mahasiswa suku Bugis yang merantau. Hasil analisis menunjukkan bahwa kemandirian memiliki sumbangan efektif terhadap variabel task commitment sebesar 39,1% dan selebihnya dipengaruhi oleh faktor lain. Mahasiswa suku Bugis yang merantau berada pada kategori task commitment yang tinggi sebesar 62,5%, dan 37,5% pada kategori task commitment sedang. Mahasiswa yang memiliki kemandirian berpengaruh terhadap tingginya task commitment yang dimiliki mahasiswa suku Bugis di perantauan.